Bone corticalization requires local SOCS3 activity and is promoted by androgen action via interleukin-6. Issue 1 (December 2017) - Cho, Dae-Chul; Brennan, Holly; Johnson, Rachelle; Poulton, Ingrid; Gooi, Jonathan; Tonkin, Brett; McGregor, Narelle; Walker, Emma; Handelsman, David; Martin, T.; Sims, Natalie
Abstract Long bone strength is determined by its outer shell (cortical bone), which forms by coalescence of thin trabeculae at the metaphysis (corticalization), but the factors that control this process are unknown. Here we show that SOCS3-dependent cytokine expression regulates bone corticalization. Young male and femaleDmp1Cre.Socs3 f/f mice, in which SOCS3 has been ablated in osteocytes, have high trabecular bone volume and poorly defined metaphyseal cortices. After puberty, male mice recover, but female corticalization is still impaired, leading to a lasting defect in bone strength. The phenotype depends on sex-steroid hormones: dihydrotestosterone treatment of gonadectomized femaleDmp1Cre.Socs3 f/f mice restores normal cortical morphology, whereas in males, estradiol treatment, or IL-6 deletion, recapitulates the female phenotype. This suggests that androgen action promotes metaphyseal corticalization, at least in part, via IL-6 signaling. The strength of long bones is determined by coalescence of trabeculae during corticalization. Here the authors show that this process is regulated by SOCS3 via a mechanism dependent on IL-6 and expression of sex hormones.